Konstruksi dan Kontestasi Kuasa Perempuan pada Naskah Drama Les Bonnes Karya Jean Genet - Ida Bagus Gede Aric Surya Lesmana; Wening Udasmoro; Arifah Arum Candra Hayuningsih (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This research aims to portray the social categories such as social class and gender that construct the oppression experienced by women in the drama script Les Bonnes written by Jean Genet. This contestation appears as a result of an interaction between three main characters in the drama: Claire and Solange, as maids and Madame as their employer. Madame is a rich woman who treats them badly because of their social background as poor women. As a result of her treatment, Claire and Solange aim to kill their employer as the way out to be free from Madame’s oppression. They create an assassination simulation to obtain their objective. To analyze this problem, this research uses the concept of habitus, capital, and arena from the theory of cultural production of Pierre Bourdieu. The method used in this article is a textual analysis method. The material objects are the drama script, Les Bonnes. The corpus data is taken from the words, sentences, and paragraphs containing the expression correlated with the contestations of power. The data is then analyzed using the lenses from the concept of habitus and cultural arena by Pierre Bourdieu. The finding shows that the habitus forms a constant and repetitive interaction among the subjects. It is influenced by the subjects’ position based on the social capital they possess. The position is characterized by two classes: the dominant and the worker that contribute to the form of contestations in Les Bonnes.